2009
DOI: 10.2224/sbp.2009.37.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal trust and knowledge sharing: Moderating effects of individual altruism and a social interaction environment

Abstract: The relationship between interpersonal trust and knowledge sharing was explored, along with the impact of individual altruism and a social interaction environment. Participants were employees in Taiwanese high-tech industries. Employees' perceived interpersonal trust, of either their colleagues or supervisor, was found to be positively correlated with their knowledge-sharing behaviors in the workplace. Employees' altruism traits were found to be a factor for them to share knowledge in the workplace and the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 12 publications
11
52
1
Order By: Relevance
“…This finding is consistent with several studies that have found altruism to be an important autonomous intrinsic motivation for knowledge sharing (e.g. Wu et al 2009;Ma and Chan 2014). On the other hand, another type of altruistic behaviour is related to organizational commitment.…”
Section: Perceived Benefitssupporting
confidence: 92%
“…This finding is consistent with several studies that have found altruism to be an important autonomous intrinsic motivation for knowledge sharing (e.g. Wu et al 2009;Ma and Chan 2014). On the other hand, another type of altruistic behaviour is related to organizational commitment.…”
Section: Perceived Benefitssupporting
confidence: 92%
“…An effective communication about a trusting attitude, a common vision of the details of the relationship, e.g. knowledge sharing, are important predictors of interpersonal trust [Wu et al 2009;Hsu and Chang 2014], which in turn enhances people's commitment to cooperation and team work efficiency [Paul and McDaniel Jr. 2004;Muethel, Siebdrat, and Hoegl 2012] and finally can lead to the success of a trust-based IOR [Fink, Kessler, and Rößl 2007]. The diversity of interpersonal trust in small groups (teams) may lead to a negative effect, frustration and a low engagement in inter-organizational cooperation [Ferguson and Peterson 2015].…”
Section: Interpersonal Trustmentioning
confidence: 99%
“…Some previous empirical research (e.g., Shah, 1998) has also used only one item to measure interpersonal trust. Moreover, more recent studies (Wu et al, 2009;Oh and Park, 2011), suggest that workers' interpersonal trust can be measured in terms of trust in supervisors and trust in co-workers. The unidimensionality of the scale was tested using principal components analysis with varimax rotation, which resulted in a single factor with a value in excess of the unit that explained 75.182 percent of the total variance.…”
Section: Interpersonal Organizational Trust We Used Two Indicators Fmentioning
confidence: 99%